2019 Annual trends and outlook report: Gender equality in rural Africa: From commitments to outcomes - Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Njuki, Jemimah (International Food Policy Research Institute, 2019)
Gender-sensitive policy and programming have an integral role to play in fostering inclusive agricultural growth to meet the commitments of African countries to the Malabo Declaration goals. The 2019 Annual Trends and Outlook Report from ReSAKSS applies a gender lens to key issues that must be addressed to fully achieve these goals. Chapters examine the intersections between gender and (1) the context and institutions within which rural people operate; (2) the natural resources that men and women depend on for agriculture, sources of vulnerability, and resilience to shocks; (3) assets and income; and (4) livelihood strategies and well-being. The report serves as the official M&E report for the Comprehensive Africa Agriculture Development Programme (CAADP), tracking progress on over 30 CAADP indicators.